Digital payments, transaction costs, and household resilience in Sub-Saharan Africa - Yao, Becatien (Kansas State University, 2019)
The weak participation in output markets and poor access to risk management tools for farm and non-farm enterprises stand as major impediments to the sustainable provision and access to food in developing countries. Rural households incur substantial transaction costs to reach output markets. In addition to their effect on market access, high transaction costs could also hinder the delivery of financial services that could presumably enable efficient risk management. Thanks to their low cost, security and rapid delivery features, digital payments present tremendous potential to improve the rural enterprise environment. However, little evidence is known about the potential role of digital payments in output market efficiency and risk management. Essay 1 focuses on digital payments and market participation while Essay 2 explores how digital payments can contribute to building resilience to income shocks. In Essay 1, we develop and test a conceptual model in which digital payments improve market participation by lowering transaction costs. Here we show that the use of mobile money is associated with a reduction of information asymmetry around the buyer type and a large gain in welfare for distant market participants. The predictions of the conceptual model are empirically tested using an instrumental variable approach and secondary data from a cross-sectional survey conducted by the Consultative Group to Assist the Poor (CGAP) in Cote d’Ivoire and Tanzania. A special regressor model estimates the probability of distant market participation increases on average by 55 percentage points for mobile money users. Furthermore, we rank marketing venues based on hold-up risk and find that the effect of mobile money is most prominent for decisions to switch from village to local market sales outlets. Our results demonstrate how farm and non-farm enterprise owners would benefit from the spread and access to digital payments beyond the traditional pathway of credit, savings, and remittances. Essay 2 attempts to understand how digital payments enhance risk management capabilities and contribute to building household resilience to future shocks. Our outcome of interest is the Barret and Constas (BC) development resilience measure that embodies the capacity of a household to avoid falling below a threshold poverty level in the face of shocks and stressors. We first construct a multidimensional index of well-being based on productive asset holdings and empirically investigate the effect of mobile money on household development resilience using a conditional moment approach. The dataset exploited consists of secondary data from a 4 rounds panel of households representative of the national population of Kenya. We found that a 10 km reduction in the distance separating households from the nearest mobile money retailer results in a percentage point increase in development resilience. Moreover, wealthier households are more likely to benefit from higher access to mobile money. When facing severe shocks, mobile money users were found capable of sustaining a higher probability of exceeding the asset poverty line than their non-user counterparts. The findings of Essay 2 establish new evidence on the long-run effect of digital payments.
Keywords: Mobile money; Transaction cost; Resilience; Market participation; Digital technologies in agriculture; Development